(3HMhK GdYedjGJ (B/s - (3HhbQI, QGHMs ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2009)
(3jVe Md eSGFd GdHQeLI GdNWjI HjGfjG, GSJYeGd GdWQjbI GdeHSWI dMd eSGFd GdHQeLI GdNWjI HGSJYeGd WQjbI GdSeHdcS, GdeSGFd GdKfGFjI aj GdHQeLI GdNWjI, eTGcd Gdfbd hGdJNUjU, JMdjd GdTHcGJ, GSJYeGdGJ hJWHjbGJ HMhK GdYedjGJs
(3GdeQGLY U(B.335s
Keywords: (3GdHQeLIs; (3GdHQeLI GdNWjIs; (3GdQjGVjGJ GdJWHjbjIs; (3HMhK GdYedjGJs